SCIENCE AND PROFESSIONAL PRACTICE IN CLINICAL PSYCHOLOGY. PSYCHOTHERAPIES AND PSEUDO-THERAPIES IN SEARCH OF SCIENTIFIC EVIDENCE - Juan A. Morian; Mario Gálvez-Lara (Papeles del psicólogo, 2020)
Psychology is considered to be a scientific discipline, but some of its specialties, such as clinical psychology, have significant difficulties in applying the scientific method, and in transferring the results of experimental research into the professional context. This situation is especially problematic when a multitude of theories fosters the proliferation of numerous treatments, as well as the (erroneous?) idea that all of them work. The confrontation between stances based on the common aspects of psychotherapies and those focused on techniques has opened up a path for pseudotherapies and their expansion, along with the confusion of the general population. This situation takes place within a context in which there was already significant disagreement between science and clinical practice that impacts many professional areas within psychology. The debate about the efficacy and the assumption that all treatments are effective enables the maintaining of a permissive attitude towards the use of any treatment, sometimes even supported by some universities, professional associations, and scientific-professional societies, without restraints on the dissemination of pseudoscientific proposals that have not yet been empirically tested. This work analyzes the current state and discusses some of its most important aspects.